2011
DOI: 10.1016/j.childyouth.2011.04.018
|View full text |Cite
|
Sign up to set email alerts
|

Toward a cumulative ecological risk model for the etiology of child maltreatment

Abstract: The purpose of the current study was to further the integration of cumulative risk models with empirical research on the etiology of child maltreatment. Despite the well-established literature supporting the importance of the accumulation of ecological risk, this perspective has had difficulty infiltrating empirical maltreatment research and its tendency to focus on more limited risk factors. Utilizing a sample of 842 mother-infant dyads, we compared the capacity of individual risk factors and a cumulative ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
105
0
16

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 161 publications
(131 citation statements)
references
References 49 publications
(67 reference statements)
10
105
0
16
Order By: Relevance
“…Ik heb lage opleiding, werkloosheid, alleenstaand ouderschap en zelf slachtoffer zijn van kindermishandeling genoemd, maar er zijn er uiteraard meer. Onderzoek wijst ook uit dat de cumulatie van verschillende risicofactoren de kans op kindermishandeling aanzienlijk vergroot (Brown, Cohen, Johnson, & Salzinger, 1998;MacKenzie, Kotch, & Lee, 2011). Als we dit vertalen naar de praktijk, dan ontstaat er echter een probleem.…”
Section: Risicofactorenunclassified
“…Ik heb lage opleiding, werkloosheid, alleenstaand ouderschap en zelf slachtoffer zijn van kindermishandeling genoemd, maar er zijn er uiteraard meer. Onderzoek wijst ook uit dat de cumulatie van verschillende risicofactoren de kans op kindermishandeling aanzienlijk vergroot (Brown, Cohen, Johnson, & Salzinger, 1998;MacKenzie, Kotch, & Lee, 2011). Als we dit vertalen naar de praktijk, dan ontstaat er echter een probleem.…”
Section: Risicofactorenunclassified
“…A cumulative approach to the study of risks assumes that child outcomes are affected by the increased stress caused by additional risk factors, regardless of the specific nature of these risks (DeaterDeckard, Dodge, Bates, & Petit, 1998). Studies supporting this approach have generally concluded that developmental difficulties tend to increase with the number of risk factors (Hooper, Burchinal, Roberts, Zeisel, & Neebe, 1998;Jaffe, Capsi, Moffitt, Polo-Tomás, & Taylor, 2007;MacKenzie et al, 2011). Pioneers in this approach, Sameroff et al (1987) found that each additional risk factor resulted in an average decrease of four verbal intelligence quotient (IQ) points in the Rochester Longitudinal Study, which evaluated 215 four-year-old children from socially heterogeneous environments.…”
Section: Socioeconomic and Psychosocial Adversity In Inuit Mothersmentioning
confidence: 99%
“…The study of individual risk factors, i.e., any situation or environmental characteristic that raises the likelihood of developing adverse outcomes, does not well represent personal experience because people tend to experience multiple risk factors at the same time (Chmura Kraemer, Stice, Kazdin, Offord, & Kupfer, 2001;Kelley et al, 2010;MacKenzie et al, 2011). A cumulative approach to the study of risks assumes that child outcomes are affected by the increased stress caused by additional risk factors, regardless of the specific nature of these risks (DeaterDeckard, Dodge, Bates, & Petit, 1998).…”
Section: Socioeconomic and Psychosocial Adversity In Inuit Mothersmentioning
confidence: 99%
“…practices (MacKenzie, Kotch, & Lee, 2011;Whitaker, Orzol, & Kahn, 2006). Family stress theory proposes that socioeconomic stressors indirectly affect the development of young children through the stress and distress experienced by their mother (Ewart & Suchday, 2002;Kotchick, Dorsey, & Heller, 2005;Westbrook & Jones Harden, 2010).…”
Section: Socioeconomic and Psychosocial Adversity In Inuit Mothersmentioning
confidence: 99%